2017
DOI: 10.6063/motricidade.6886
|View full text |Cite
|
Sign up to set email alerts
|

Motor competence in preschool children’s: An analysis in private and public school children

Abstract: ARTIGO ORIGINAL | ORIGINAL ARTICLE RESUMOO objetivo deste estudo foi comparar a competência motora de pré-escolares em diferentes ambientes, a saber, escolas particulares e públicas da cidade do Recife-PE, Brasil. A amostra contou com 292 crianças de 3 a 5 anos de idade proporcionalmente distribuídas em escolas públicas e particulares da cidade do Recife-PE. A avaliação da competência motora foi realizada com o Test of Gross Motor Development -2 (TGMD-2). Posteriormente, os grupos foram formados de acordo com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…According to our study, the fact of having facilities for playing and sports practice, both inside and outside school, positively moderates the associations, allowing improvement in motor competence, which could contribute to children being more active in their adult life. It is important to understand that the school context and conditions can play an important role in a child's motor development, providing adequate and enriching motor opportunities (Chaves et al, 2015;Queiroz et al, 2016). In this scenario, the information obtained in the moderation analysis seems to attenuate the possible harmful impacts throughout the life cycle, considering that children inserted in the better contexts seemed protected of the deleterious impact of BMI on motor competence scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our study, the fact of having facilities for playing and sports practice, both inside and outside school, positively moderates the associations, allowing improvement in motor competence, which could contribute to children being more active in their adult life. It is important to understand that the school context and conditions can play an important role in a child's motor development, providing adequate and enriching motor opportunities (Chaves et al, 2015;Queiroz et al, 2016). In this scenario, the information obtained in the moderation analysis seems to attenuate the possible harmful impacts throughout the life cycle, considering that children inserted in the better contexts seemed protected of the deleterious impact of BMI on motor competence scores.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, each specific context could shape the motor competence and development of physical activity in children and adolescents (Venetsanou and Kambas, 2010;Barnett et al, 2013;Queiroz et al, 2016;True et al, 2017;Zeng et al, 2019). Some prior studies have identified different environmental contexts, such as type and size of the school, physical environment, activities structured in adequate spaces within the school, playgrounds outside the school, and places for sports practice (Barnett et al, 2016;Tonge et al, 2016) that may specifically influence the development of motor competence (Newell, 1986;Chaves et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Em relação ao ambiente escolar, Queiroz et al (2016) e Cotrim et al ( 2011) demostraram que crianças de escolas privadas apresentaram uma competência motora superior comparadas com aquelas que frequentam escolas públicas, especificamente nas habilidades de controle de objetos e desempenho motor geral. Cotrim et al (2011) enfatizaram que crianças provenientes da escola privada tem mais oportunidades adequadas, tais como conteúdo específico, instrução e local apropriados, acesso e disponibilidade de material e equipamentos, que favoreceram o pleno desenvolvimento motor; por outro lado, crianças provenientes da escola pública que não têm um ambiente propício e oportunidade sistematizada e estruturada para o desenvolvimento das habilidades motoras podem ficar defasadas em termos motores, sendo que a falta de infraestrutura, espaços reduzidos e carência de materiais minimizam as possibilidades de uma alta competência motora.…”
Section: Discussionunclassified
“…An important finding of this study is that children from private schools obtained higher scores, both in the LDCDQ-BR total and sub-scores (Table 2). In Brazil, private schools usually offer more stimulating environments and activities for motor development (Queiroz et al, 2016). Furthermore, more children from private schools (52.2%) participated in extra-class motor activities, compared with children from public schools (10.9%).…”
Section: Discussionmentioning
confidence: 99%